Integrating community capitals into water quality and natural resource preservation and protection - Davis, Sherry (Kansas State University, 2009)
The Healthy Ecosystems-Healthy Communities (HEHC) project works with communities to assess and protect their local natural resources using a public engagement process. It moves water quality to the forefront of community decision-making by linking investment in water quality BMPs and activities to additional community capital benefits. Cornelia and Jan Flora (2008) with the North Central Regional Center for Rural Development, at Iowa State University, found that successful, sustainable communities paid attention to seven types of community assets or "capitals": natural, cultural, human, social, political, financial and built. They also discovered that community investment in one capital could be used to build assets in other capitals, creating a more sustainable approach to community improvement. The HEHC program utilizes the concept of multiple capitals "investment and benefit" to encourage adoption of sustainable water quality programs, BMPs, and educational activities in small communities. A third-party facilitator works with community volunteers to expand their local stakeholder group, initiate public engagement, and promote citizen exploration, discovery and ownership of knowledge about the status and condition of their local resources. Armed with this knowledge, and using a public forum process, citizen groups generate water quality projects ideas and activities that are appropriate for their community. These ideas are then further explored to evaluate each project for ways to create additional benefits to their community’s other assets. The multiple capitals methodology is successful because it expands opportunities for stakeholder involvement. The Healthy Ecosystems-Healthy Community program also integrates water quality into existing community values and visions which promotes a sustainable, community-driven program for water and natural resource protection.
Keywords: Water quality; Healthy Ecosystems-Healthy Communities Program; Public engagement